Efficient chemical fixation of CO2 into cyclic carbonates using poly(4-vinylpyridine) supported iodine as an eco-friendly and reusable heterogeneous catalyst - Khaligh, Nader Ghaffari; Mihankhah, Taraneh; Johan, Mohd Rafie (Wiley, 2018)
Green and sustainable synthesis is considered as a safer alternative to the conventional synthetic processes owing to its environmental friendly nature, atom economy, cost-effectiveness, and easy handling. Herein, the catalytic efficiency of poly(4-vinylpyridine) supported iodine (P4VP/I 2 ) as a metal-free and organocatalyst system was studied and approved for an efficient chemical fixation of CO 2 into cyclic carbonates which is performed via the coupling of CO 2 with epoxides. The high conversion and excellent selectivity were obtained for a broad range of epoxides in the presence of catalytic amount of P4VP/I 2 under solvent-free conditions. The heterogeneous catalyst could be recovered and regenerated over several times with no significant loss of catalytic activity. The possible mechanism was described for the catalytic performance of P4VP/I 2 based on the synergetic effect of the Lewis acid and base sites and nucleophilic anion.